Assessing building surveyor roles in property maintenance and management scope of work / Ahmad Saffian Ahmad Kassim - Ahmad Kassim, Ahmad Saffian (Faculty of Architecture, Planning and Surveying, 2014)
Building surveyors (BS) are professional that have knowledge in handling building materials, understanding construction techniques, methods and technology skills. Building Surveyor is still very new as compared to other construction players, BS is still without an Act but govern under professional body. BS courses been taught in universities all over Malaysia is been recognized by RICS. There a demand for systematic approach in the industry towards building control and maintenance, BS is introduced to fulfill that requirement. BS has four (4) major areas which is building control, building inspection, building maintenance and building insurance as specified by RISM. This research is about assessing Building Surveyor (BS) roles in Property Maintenance and Management Organization (PMMO). The aim of this research is to recognize the acceptance of Building Surveyors profession in Property Maintenance and Management Organization in Malaysia. This research employed both secondary and primary data. The data collected is by distributing questionnaires to employee and employer at PMMO and were presented using pie chart, bar chart using frequency, percentages and means score. The questionnaires cover 2 aspects of area which is BS roles in building maintenance including required scope necessary to support maintenance comprises of building control, building inspection, building insurance and BS competencies in PMMO. For competencies, respondents were found to have honed the skill and competencies required and their employers verify it. Both result shows that BS have significant roles and practiced skill to work in PMMO. Therefore this study suggested that BS has future roles in the industry.